OPTIMALISASI LAHAN PEKARANGAN MELALUI KEBUN GIZI: STRATEGI PENINGKATAN AKSES PANGAN BERGIZI DI TINGKAT KELUARGA - Malika Nur Hasanah; Suci Oktavianti; Nurhayati; Raiisa Aqilah; Tazkia Aisya Karen; Titin Dwi Aryani; Rahmi Fitri J (Departement of Environmental Health, Faculty of Public Health, Sriwijaya University, 2025)
Home yards remain underutilized as a source of family nutrition, including in Baru Rambang Village. This program aimed to improve access to nutritious food through household-based nutrition gardens using the Asset-Based Community Development (ABCD) approach. Cucumbers and green beans were planted in 150 polybags at the local health post with community involvement. The results showed improved gardening skills, productive yard use, and interest in replicating gardens at home. Nutrition gardens proved effective in supporting sustainable household food security.